Cortical neuronal mechanisms of sleep homeostasis. - Vyazovskiy, V (2013)
The longer we are awake, the deeper is our subsequent sleep. On the other hand, the shorter and more fragmented is our sleep, the more difficult it is for us to maintain wakefulness and stable cognitive performance the next day. This relationship between wakefulness and subsequent sleep becomes especially apparent after sleep deprivation or during chronic sleep restriction, which is experienced by millions of people in our society, as well as in multiple neurological, respiratory and other chronic diseases. Invariably, poor sleep leads to fatigue, sleepiness, marked cognitive deficits and impaired mood. The crucial question is what happens to the brain after a period of being awake or asleep, and where in the brain and why do these changes occur. This review summarizes information about neurophysiological substrates of sleep homeostatic processes at the cellular and network levels. It is suggested that sensory, behavioral and cognitive deficits after sleep deprivation resulting from the imbalance between local and global neuronal interactions can be reversed only by physiological sleep.